Tinjauan Yuridis Tindak Pidana Penadahan Jual Beli Handphone Di Bandar Lampung (Studi Putusan Nomor 69/Pid.B/2023/ PN.Tjk.) - Ramasari, Risti Dwi; Seftiniara, Intan Nurina; Gumay, Justitia Muharram (Peneliti.net, 2024)
Article 480 1 of the Criminal Code concerning the crime of detention explains that detention is part of the property crime listed in Chapter XXX of the Criminal Code, regarding the offense of providing assistance after the crime has occurred. Detention is usually aimed at enriching oneself, one way or another, this must not be allowed, so that one can profit from crimes committed by others. Detention is always related to goods